Analisis Pengaruh Pengetahuan, Lingkungan Sosial dan Pendidikan Mahasiswa Tentang Bank Syari’ah terhadap Minat Menabung Pada Bank Syari’ah - Mutia Zalila (CV. ITTC INDONESIA, 2023)
Over time and the development of technology and knowledge in the field of Islamic banking among students which makes this development still not well understood by some of them. This study aims to determine the effect of knowledge, social environment, and education on the intention to save in Islamic banks in case studies of FEB students at Dharma Andalas University. In this study, 88 respondents were used who were randomly obtained through the solvin formula, where these respondents were FEB students at Dharma Andalas University. This type of research is quantitative research using multiple linear regression methods. The results of the study show that social environment variables have a significant effect on students' interest in saving in Islamic banks. Whereas knowledge and education variables have no significant effect on students' interest in saving at Islamic banks.